Cultura do estupro, representações de gênero e direito - Lima, Lana Lage da Gama (2017)
The term “rape culture” emerged in the 1970s amid the North-American Feminist Movement to characterise the cultural environment in which laws, norms, values and practices promote and naturalize sexual violence against women, because of gender inequality and sexist social representations. Although this particular view is recent, rape culture is old and, in the Western world, has deep roots in the Judeo-Christian tradition and its dichotomic representation of women, which is based on two powerful symbols existing in the popular imagination: Eve and Mary. This paper evaluates rape culture as a long historical phenomenon, identifying its roots in religious and legal documents produced between the 3rd and the beginning of the 20th century.